Logos, hospitalidad y democracia : volver al origen de Europa de la mano de Augusto Del Noce y San Benito - Posse, Carolina Riva (Sapientia, 2019)
In this article the Rule of Saint Benedict, in the chapter related to the welcome of guests, is the starting point to talk about hospitality, identifying the salient features which fostered the formation of Europe. The search for Lógos, the exercise of reason open to transcendence, attention to the other, constitute key concepts to reappropiate the traditional spirit born in the Christian synthesis, and which is to be continuously renewed. Del Noce helps to understand how the actual crisis is the product of a battle against all forms of transcendence.